Observations of near‐inertial energy in Lake Superior. (22nd March 2013) - Austin, Jay
Abstract : Directly measured velocity data collected in Lake Superior between 2008 and 2011 show that currents in the open waters of the lake are dominated by near‐inertial energy. The near‐inertial signal is composed almost entirely of clockwise rotation, with vertical structure dominated by the first baroclinic mode, where waters above and below the thermocline are roughly 180° out of phase with each other. The strength of the oscillations is strongly related to the strength of the stratification; in periods of the year when the water column is well‐mixed (typically late autumn and late spring) the near‐inertial signal is very weak; when stratification exists, near‐inertial oscillations can occur. Combining the velocity amplitudes with an estimate of the thermocline displacement allows estimation of the dominant direction and horizontal wavelength of the near‐inertial field, showing that horizontal wavelengths are on the order of 50–100 km, and the direction of the waves veers counter‐clockwise over the course of the season with a period of ∼ 1 month. Observations of backscatter suggest that inertial oscillations may be responsible for re‐suspension of bottom sediments, which could have significant ecological consequences.